Semisynthetic triterpenes led to the generation of selective antitrypanosomal lead compounds. (31st March 2022) - Guilhon‐Simplicio, Fernanda; Serrão, Carlos Klinger Rodrigues; Pinto, Ana Cristina da Silva; Pacheco, Paulo Anastácio Furtado; Faria, Robson Xavier; da Rocha, David Rodrigues; Ferreira, Vitor Francisco; Pereira‐Junior, Raimundo Carlos; Matheeussen, An; Baán, Adrienn; Kiekens, Filip; de Meneses Pereira, Maria; et al.
Abstract: Triterpenes α, β‐amyrin are naturally occurring molecules that can serve as building blocks for synthesizing new chemical entities. This study synthesized acyl, carboxyesther, NSAID, and nitrogenous derivatives and evaluated their antimicrobial activity. A cyclodextrin complexation method was developed to improve the solubility of the derivatives. Of the 17 derivatives tested, five exhibited activity against Trypanosoma cruzi, T . brucei, Leishmania infantum, Candida albicans, Staphylococcus aureus, and Escherichia coli . The 9a/9b mixture showed weak activity against the parasites (IC50 24.45–40.32 μM). However, it showed no activity for the other microorganisms. Derivatives 14a/14b exhibited potent activity against T . cruzi (IC50 2.0 nM) in this tested concentration did not show activity to the other microorganisms and were not cytotoxic. Derivatives 15a/15b and 16a/16b demonstrated relevant activity against the parasites (IC50 2.24–5.44 μM), but were also cytotoxic. Derivatives 17a/17b showed low activity against the tested parasites (IC50 21.70–22.79 μM), but they were selective since they did not show activity against other microorganisms. In docking studies, in general, all derivatives showed complementarity with the CYP51 binding site of the trypanosomatid mainly by hydrophobic interactions; thus, it is not conclusive that the molecules act by inhibiting this enzyme. Our results showed that triterpenes derivatives with antitrypanosomal activity could be synthesized by an inexpensive and rapid method. Abstract : Derivatives of α, β‐amyrins showed potent activity against trypanosomatids. Complexation with sulfobutylether‐β‐cyclodextrin increasing their solubility. α, β‐amyrins may be a promising and inexpensive source of anti‐trypanosomatid.